Nartj Katitj Bidi Ngulluckiny Koorl? (Which Knowledge Path Will We Travel?) - Collard, Len; Harben, S. (University of Western Australia, 2010)
Despite our long history and our constant presence, 'Nyungar' experiences and achievements are underrepresented in the historiography of the South West. Various writers have critiqued the minimal recognition of 'Nyungar', 'Murri' and 'Koori' ideology and theories within social science. Calls from Indigenous Australians for historical works reflecting their experiences and concerns are mirrored globally in countries such as New Zealand, South Africa, the United States and Canada. For example, Mason Durie wrote of the Maori reclaiming their histories through their writing. In this article, we touch on some of the significant differences in history as it is told or written by 'Nyungar' and as it is told or written by 'wedjela' (a 'Nyungar' rendition of the term 'white fellow'). In thinking about doing research, and asking others to think more deeply about their research and writing, we also point to ways in which 'wedjela' history might reflect more 'Nyungar' experiences and concerns.